Switching Ripple Harmonics Attenuation in DFIG and Matrix Converter-Based WECS - Gytis Svinkunas (MDPI AG, 2021)
The analysis presented in this paper is focused on the harmonics distortion damping in the case of bidirectional power-flow of the electronics device—matrix converter as an interface between two power sources. Bidirectional energy flow takes place in the matrix converter that is used in renewables, hybrid transformers, microgrids, etc. It is observed that the matrix converter generates sinusoidal voltage with some amount of harmonic distortion and worsens in the quality of power in the utility grid. Taking into account the bi-directional energy flow and the matrix converter operation principle, four key requirements for the filters are formulated. Six theoretically possible filter topologies are investigated for compliance with these requirements. Two of the filter topologies are recognized as complying with these requirements and applicable for the switching ripple harmonics damping in the utility grid connected matrix converter in the case of bidirectional power flow. The suitability of these topologies was verified by MATLAB/Simulink simulation. Using the proper filter topology will significantly reduce the size, weight and cost of the components of the filter, as well as the utility grid’s pollution by switching ripple harmonics. It is appropriate to apply such filters to matrix converters that operate in wind turbines installed in doubly fed induction generators. These filters should also be used in hybrid transformers and other high-power devices with matrix converters.